Tracking the dragon : national intelligence estimates on China during the era of Mao, 1948-1976 - prepared under the auspices of Ambassador Robert L. Hutchings, Chairman, National Intelligence Council. (Government Printing Office, 2004)
Includes bibliographical references. Donation of Christian Friedrich Ostermann.